Granulosa Cell Tumor Associated with Occult Hyperadrenocorticism in a Yorkshire Terrier Bitch - Deluchi, Priscilla; Ledur, Gabriela Reis; Pavarini, Saulo Petinatti; Pöppl, Álan Gomes (Acta Scientiae Veterinariae, 2018)
Background: Hyperadrenocorticism (HAC), is considered a set of symptoms due to excessive exposure to cortisol. Naturally occurring HAC is most often related to pituitary tumors (pituitary-dependent HAC - PDH). Occult HAC, is referred as a clinical picture highly consistent with HAC; however, routine screening tests are negative. In addition, one or more steroids are elevated following administration of adrenocorticotrophic hormone (ACTH). Ovarian granulosa cell tumors, can produce steroids leading to paraneoplastic syndromes. The objective of this study was to report an unpublished case of ovarian granulosa cell tumor associated with occult hyperadrenocorticism in a Yorkshire Terrier. Case: A 13-year-old intact female dog, Yorkshire Terrier, was brought for consultation with slight weight loss, polyuria, polydipsia, irregular estrous cycles, increased abdominal volume and thin coat. On physical examination the animal was gasping and presented severe periodontal disease, bulging abdomen, alopecia and skin hyperpigmentation. Complete blood count presented no changes; however, serum biochemistry evaluation highlighted hyperalbuminemia, hypertriglyceridemia, alkaline phosphatase increased activity, and urinary specific gravity and creatinine below reference values. On abdominal ultrasonography left adrenal gland measured 2.08 cm x 1.08 cm and the right adrenal gland measured 2.11 cm x 0.84 cm, indicating bilateral adrenomegaly compatible with PDH. In the hypogastric abdomen, a large heterogeneous hypoechogenic mass was also observed, with areas of cystic cavities, measuring 5.80 cm x 7.30 cm. A low dose dexamethasone suppression test (LDDST) was performed, due to PDH suspicion. The test did not confirm HAC, suspecting, then, to be a case of occult/atypical HAC. Due to the strong clinical suspicion, and owner financial problems for further investigated occult HAC, trilostane treatment was initiated. Approximately one month after starting treatment, an ACTH stimulation test (AST) for cortisol and 17-hydroxyprogesterone (17-OHP) determination was performed, revealing high values for both hormones. Exploratory laparotomy was indicated due to the tumor image on hypogastric region visualized on abdominal ultrasonography. A cranial pole mass of the left ovary measuring 8.5 x 7.0 x 4.5 cm, of friable consistency and brownish color, was removed through ovariohysterectomy. A granulosa cell tumor on left ovary, as well as leiomyoma and cystic endometrial hyperplasia in the uterus, became clear through histopathological examination. Trilostane treatment was sustained after surgery. Few weeks later, the patient presented a clinical picture suggestive of hypoadrenocorticism, associated with a low sodium:potassium ratio (25:1), and AST results (basal and post-ACTH cortisol) below reference range, confirming Addisonian´ crises. The patient deceives within two days. Discussion: Granulosa cell tumors can produce estrogen and progesterone, as well as other steroids, leading to paraneoplastic syndromes with peculiar clinical presentations. Steroids transport in plasma occurs via specific carrier proteins. Increased production of other steroid hormones may result in higher concentration of free cortisol, thus leading to clinical manifestations of hypercortisolism. As 17-OHP is one of the precursors in cortisol synthesis and has been shown elevated on AST, it can be assumed that altered steroid hormone levels due to the granulosa cell tumor interfered on cortisol biodisponibility, leading to HAC signs. Dexamethasone suppression test results indicated that pituitary-adrenal axis was responsive to negative feedback. The Addisonian crises after tumor removal indicate that the main source for systemic excessive cortisol effects was the eminent steroid secretion by the granulosa cell tumor.